Articulation in the concerto for Horn No 3 K447 by Wolfgang Amadeus Mozart: Case study the analysis of the solo horn part in the first movement / Mohd Faris Romzy - Romzy, Mohd Faris (2014)
The excerpt was taken from the Cambridge Mozart Encyclopedia. Mozart's contribution in the concerto repertoires is really well known, and almost all musicians know Mozart. His concertos are good representatives for the late eighteenth-century concerto. Wolfgang Amadeus Mozart was born in Salzburg on the 27th of January 1756 and died in Vienna on the 5th of December 1791. He was baptized with the name Johannes Chrysostomus Wolfgangus Theophilus Mozart. Soon after that, Theophilus (beloved of God) was changed to Amade. As a child prodigy he started to play at the age of four. He started to play games in music, sitting with his sister at the keyboard, playing on the keys. (Melograni, 2007) He really started to play the harpsichord seriously at the age of four, composing at five and playing the violin and the organ at the age of six. His earliest education was provided by his father, Leopold Mozart